Determination of hindered phenolic antioxidants in plastic packaging injections by magnetic solid phase extraction followed by high performance liquid chromatography. Issue 2 (5th December 2014) - Liao, Wenlong; Chen, Anyi; Yang, Yaling
Abstract : A simple and effective method based on magnetic solid-phase extraction combined with high performance liquid chromatography was used for the determination of hindered phenolic antioxidants in plastic packaging injections. Abstract : A simple and effective method based on magnetic solid-phase extraction combined with high performance liquid chromatography was used for the determination of hindered phenolic antioxidants in plastic packaging injections. The extraction and clean-up via Fe3 O4 @CTAB magnetic adsorbent dispersion in injections was followed by magnetic isolation and desorption of the analytes using acetonitrile. The cationic surfactant cetyltrimethylammonium bromide (CTAB) coated on the surface of Fe3 O4 nanoparticles adsorbent was synthesized. The main parameters affecting the adsorption recoveries were evaluated and optimized, including the amounts of surfactant and adsorbent, pH, ionic strength, desorption conditions, and sample volume. Under the optimum conditions, the method was successfully applied to the determination of hindered phenolic antioxidants in plastic packaging injections. Low limits of detection (LODs) of 0.14 and 0.15 µg mL −1 and limits of quantification (LOQs) of 0.45 and 0.50 µg mL −1 were achieved. The mean recoveries were in the range from 85.0% to 93.5% at 5, 10, and 20 µg mL −1 spiked levels, and the relative standard deviations (RSDs) were in the range from 1.16% to 2.81%.